Cash flow management and its implication on the performance of the selected medium scale manufacturing companies / Nor Azlin Mahani Mohamad - Mohamad, Nor Azlin Mahani (1993)
Cash flow problem is one of the major causes of business failure. Cash is commonly referred to as the 'bottomline' and for good reasons a sudden cash deficiency can quickly turn a profitable operation into a losing venture. The lack of cash are resulted from poor cash management and control by business owners who do not understand the role cash plays in business. It is felt that a sound cash flow is the result of a healthy management of working capital.